Blocking interferon γ reduces expression of chemokines CXCL9, CXCL10 and CXCL11 and decreases macrophage infiltration in ex vivo cultured arteries from patients with giant cell arteritis. Issue 6 (23rd December 2015) - Corbera-Bellalta, Marc; Planas-Rigol, Ester; Lozano, Ester; Terrades-García, Nekane; Alba, Marco A; Prieto-González, Sergio; García-Martínez, Ana; Albero, Robert; Enjuanes, Anna; Espígol-Frigolé, Georgina; Hernández-Rodríguez, José; Roux-Lombard, Pascale; et al.
Abstract : Background: Interferon γ (IFNγ) is considered a seminal cytokine in the pathogenesis of giant cell arteritis (GCA), but its functional role has not been investigated. We explored changes in infiltrating cells and biomarkers elicited by blocking IFNγ with a neutralising monoclonal antibody, A6, in temporal arteries from patients with GCA. Methods: Temporal arteries from 34 patients with GCA (positive histology) and 21 controls were cultured on 3D matrix (Matrigel) and exposed to A6 or recombinant IFNγ. Changes in gene/protein expression were measured by qRT-PCR/western blot or immunoassay. Changes in infiltrating cells were assessed by immunohistochemistry/immunofluorescence. Chemotaxis/adhesion assays were performed with temporal artery-derived vascular smooth muscle cells (VSMCs) and peripheral blood mononuclear cells (PBMCs). Results: Blocking endogenous IFNγ with A6 abrogated STAT-1 phosphorylation in cultured GCA arteries. Furthermore, selective reduction in CXCL9, CXCL10 and CXCL11 chemokine expression was observed along with reduction in infiltrating CD68 macrophages. Adding IFNγ elicited consistent opposite effects. IFNγ induced CXCL9, CXCL10, CXCL11, CCL2 and intracellular adhesion molecule-1 expression by cultured VSMC, resulting in increased PBMC chemotaxis/adhesion. Spontaneous expression of chemokines was higher in VSMC isolated from GCA-involved arteries than in those obtained from controls. Incubation of IFNγ-treated control arteries with PBMC resulted in adhesion/infiltration by CD68 macrophages, which did not occur in untreated arteries. Conclusions: Our ex vivo system suggests that IFNγ may play an important role in the recruitment of macrophages in GCA by inducing production of specific chemokines and adhesion molecules. Vascular wall components (ie, VSMC) are mediators of these functions and may facilitate progression of inflammatory infiltrates through the vessel wall.